Impacts of loading thymoquinone to gold or silver nanoparticles on the efficacy of anti-tumor treatments in breast cancer with or without chemotherapeutic cisplatin - Soha Gomaa; Mohamed Nassef; Ahlam Abu-Shafey; Mona Elwan; Asmaa Adwey (BMC Biotechnology)
Abstract Background Nanotechnology has been greatly examined for tumor medication, as nanoparticles (NPs) serve a crucial role in drug delivery mechanisms for cancer therapy. In contrast to traditional cancer therapies, NPs-based drug delivery offers several benefits, including increased stability and biocompatibility, improved retention capabilities and permeability, as well as precise targeting. Aim The objective of this study was to examine the tumor-targeting efficacy of Thymoquinone (TQ)–loaded gold NPs (AuNPs/TQ conjugate) or TQ–loaded silver NPs (AgNPs/TQ conjugate) in conjunction with the conventional chemotherapy agent cisplatin (CP) in Ehrlich ascites carcinoma (EAC)-bearing mice. Methods The loading capacity of synthesized conjugates was characterized by UV-Vis spectra and transmission electron microscope (TEM). We used CD-1 mice with a peritoneal EAC tumor xenograft model that received oral administration of TQ, AuNPs, AgNPs, AuNPs/TQ conjugate, and AgNPs/TQ conjugate. Methods EAC-bearing mice received daily oral administration of one of the following treatments for six consecutive days: TQ, AuNPs, AgNPs, AuNPs/TQ, AgNPs/TQ, AuNPs/TQ + CP, or AgNPs/TQ + CP conjugates. Eleven days after EAC inoculations, assessments were conducted to evaluate the total number of tumor cells, splenocytes, white blood cells (WBCs), C-reactive protein (CRP) levels, flow cytometric analysis of apoptosis in EAC cells, as well as the functionality of the kidney and liver. Results EAC-bearing mice that received treatment with TQ, AuNPs, AgNPs, AuNPs/TQ, and AgNPs/TQ exhibited significantly enhanced anti-tumor activity and improved therapeutic efficacy. Our results further revealed that the combined synergistic approach of TQ’s anti-tumor properties, along with the efficient penetration abilities of AuNPs or AgNPs, led to a significant inhibition of the growth of tumor cells in EAC tumor-bearing mice. Moreover, the incorporation of CP into the AuNPs/TQ or AgNPs/TQ conjugates substantially augmented the anti-proliferative effects against EAC tumor cells, effectively overcoming resistance to chemotherapeutic agents. Furthermore, our data revealed that this combination resulted in an elevation of leukocyte counts, along with an increase in the absolute quantities of lymphocytes, neutrophils, and monocytes, thereby activating the immune system and reducing the inflammatory marker CRP. However, the restoration of splenocyte levels, which had been reduced due to EAC cell inoculation, required an extended period to return to baseline. Furthermore, the results indicated moderate alterations in the functionality of both the liver and kidney. Conclusion To conclude, AuNPs, AgNPs, AuNPs/TQ, and AgNPs/TQ may hold great promise as potential nanoparticle-based therapies for cancer treatment. Additionally, provides numerous benefits compared to conventional cancer therapies, such as selectivity and minimal side effects. Additionally, AuNPs, AuNPs/TQ, AuNPs/TQ + CP, AgNPs, AgNPs/TQ, or AgNPs/TQ + CP can specifically target tumor tissues, suppress tumor growth, extend the lifespan of tumor-bearing mice, and minimize cytotoxic effects on normal tissues, relative to the administration of free CP alone. More research is needed to understand the mechanisms of these nanoparticle-based therapies in clinical and optimize their use as cancer therapies.